Uncoupling protein 1 expression in adipocytes derived from skeletal muscle fibro/adipogenic progenitors is under genetic and hormonal control. Issue 2 (5th February 2018) - Gorski, Tatiane; Mathes, Sebastian; Krützfeldt, Jan
Abstract: Background: Intramuscular fatty infiltration is generally associated with the accumulation of white adipocytes in skeletal muscle and unfavourable metabolic outcomes. It is, however, still unclear whether intramuscular adipocytes could also acquire a brown‐like phenotype. Here, we detected intramuscular expression of brown adipocyte markers during fatty infiltration in an obesity‐resistant mouse strain and extensively compared the potential of two different stem cell populations residing in skeletal muscle to differentiate into brown‐like adipocytes. Methods: Fatty infiltration was induced using intramuscular glycerol or cardiotoxin injection in the tibialis anterior muscles of young or aged 129S6/SvEvTac (Sv/129) mice or interleukin‐6 (IL‐6) knockout mice, and the expression of general and brown adipocyte markers was assessed after 4 weeks. Fibro/adipogenic progenitors (FAPs) and myogenic progenitors were prospectively isolated using fluorescence‐activated cell sorting from skeletal muscle of male and female C57Bl6/6J and Sv/129 mice, and monoclonal and polyclonal cultures were treated with brown adipogenic medium. Additionally, FAPs were differentiated with medium supplemented or not with triiodothyronine. Results: Although skeletal muscle expression of uncoupling protein 1 (Ucp1) was barely detectable in uninjected tibialis anterior muscle, it was drastically induced following intramuscular adipogenesis in Sv/129 mice and further increased in response to beta 3‐adrenergic stimulation. Intramuscular Ucp1 expression did not depend on IL‐6 and was preserved in aged skeletal muscle. Myogenic progenitors did not form adipocytes neither in polyclonal nor monoclonal cultures. Fibro/adipogenic progenitors, on the other hand, readily differentiated into brown‐like, UCP1 + adipocytes. Uncoupling protein 1 expression in differentiated FAPs was regulated by genetic background, sex, and triiodothyronine treatment independently of adipogenic differentiation levels. Conclusions: Intramuscular adipogenesis is associated with increased Ucp1 expression in skeletal muscle from obesity‐resistant mice. Fibro/adipogenic progenitors provide a likely source for intramuscular adipocytes expressing UCP1 under control of both genetic and hormonal factors. Therefore, FAPs constitute a possible target for therapies aiming at the browning of intramuscular adipose tissue and the metabolic improvement of skeletal muscle affected by fatty infiltration.